STRATEGI PENGEMBANGAN PEMASARAN UMKM KULINER MELALUI DIGITAL PAYMENT DENGAN METODE SEM DAN TOPSIS (Studi Kasus UMKM Kuliner Daerah Jombang) - Eka Septiana Wulandari Eka; Retno Indriartiningtias; Ernaning Widiaswanti; Ida Lumintu; Kukuh Winarso; Sabarudin Akhmad (Program Studi Teknik Industri S-1, Fakultas Teknik UPN Veteran Jakarta, 2025)
The development of culinary UMKM Jombang is currently starting to grow rapidly. With the presence of non-cash payments, it can increase efficiency and increase the success of an UMKM business. The use of e-wallets can currently help consumers be more effective, and they do not need to carry cash. Most culinary UMKM in the Jombang area have not used digital payments. To overcome this problem, a study was conducted to determine the interest in using e-wallets among culinary UMKM consumers in the Jombang City area. This study uses five exogenous variables consisting of the variables of perceived ease of use, trust, perceived usefulness, risk, promotion, while the endogenous variable is the intention to transact online. This study uses the Structural Equation Modeling method which is used to determine the variables that influence the selection of e-wallets. The results of SEM will be used to rank which e-wallet is the best based on consumer preferences using the TOPSIS method. Data collection in this study used a questionnaire distributed offline, with the criteria of sample respondents who had used e-wallets. The number of samples in this study used 125 respondents. The test results using SEM show that significant variables consisting of trust, usability, and promotion variables have an effect on the intention to transact online using e-wallets. The results of the TOPSIS analysis show that the best e-wallet is Dana, followed by Shopeepay, LinkAja, Gopay, and Ovo.